The efficiency of Pistacia atlantica gum for increasing resistance of rapeseed oil-heat treated wood to fungal attacks - Mahmoud Kia, Morad; Tarmian, Asghar; Naghi Karimi, Ali; Gholamiyan, Hadi; Abdulkhani, Ali; Reza Mastri Farahani, Mohamad (Maderas. Ciencia y Tecnología, 2020)
In this research, we used Pistacia atlantica gum during cooling phase of oil-heat treatment of poplar wood (Populus deltoids) to improve its resistance to the white-rot fungus Trametes versicolor and growth of the mold fungus Penicillium expansum. Thermal modification was carried out using rapeseed oil at 180 °C, 200 °C and 220 °C for 2 hours and 4 hours. The modified wood specimens were then directly cooled in the oil containing 0 %, 5 % and 10 % (w/w) of the gum at 25 °C for 30 minutes. The chemical constituents of the essential oil extracted with a Clevenger type apparatus were determined by chromatography–mass spectrometry (GC-MS). The amounts of α-pinene, β-pinene and α-terpinolene of the essential oil were 60,2 %, 8,7 % and 3,9 %, respectively. The mold resistance was greatly improved, while the improvement against the decay fungus was only observed for the specimens modified at 180 °C. Our results confirmed that the enhanced fungal resistance was not only due to the presence of monoterpenes in the essential oil, but also to a further reduction in the hygroscopicity of the treated wood.